University Teachers’ Learning Experiences During Emergency-Remote-Teaching Through a Networked Learning Lens: A Phenomenography - Acuyo Cespedes, Alejandro; Lee, Kyungmee (Proceedings of the International Conference on Networked Learning, 2024)
This paper presents part of the preliminary findings of an investigation into higher education (HE) teachers’ perceptions of personal learning networks in the context of the recent emergency-remote-teaching (ERT) scenario caused by Covid19. Technology had been increasingly permeating HE long before the pandemic, blurring the lines between online and offline spaces as students and teachers engaged across both mediums in a complex web of connections to people and online resources. The pandemic induced ERT period has magnified university teachers’ use of learning networks, as many have been forced to increasingly rely on them throughout this unexpected interruption of the HE status quo. With an absence of a coherent institutionalized approach to ERT and teachers’ professional development, there has been a great diversity of teachers’ networked learning experiences during that period. This phenomenography, therefore, explores the perceptions of 18 Academic English instructors at a leading English-instruction university in Kazakhstan that was, like many other institutions worldwide, forced to abruptly go online. The semi-structured interviews targeted the teacher’s diversified views on the benefits and challenges of network use and how these networks can be used to connect to others and online resources, using the Networked Learning lens. The present paper includes some of the preliminary findings from the ongoing research project focusing on several interlinked aspects of teachers’ perceptions and experiences of networked learning during the ERT period. The results thus far show that Academic English instructors perceive the core benefits of their network use at least in four different ways as enabling flexible access to online resources, enabling flexible access to others, facilitating personalised and focussed one-to-one pedagogical interactions (both with their colleagues and students), and maintaining and developing a sense of belonging to different academic communities (removing temporal-and-spatial barriers). The authors expect to provide more comprehensive (if not final) findings and insights during the presentation.